Physical functional performance, body composition, strength, and cognitive function in aged 60 years and older from North of Brazil - Ewertton de Souza Bezerra; Andreza dos Santos Silva; Geovanna de Paula Martins de Souza; Walbert Menezes Bitar; Jean Carlos Constantino Silva; Leandro Augusto Pereira de Souza; Jéssica Naveca de Abreu; Rômulo de Oliveira Sena; Luis Mochizuki (Archives of Gerontology and Geriatrics Plus)
This study aims to establish a set of reference data for Amazonas’ older women based in younger adult's value. Two-hundred and thirteen women did partially (handgrip strength test, 6-m walking test, and timed up and go) and 126 did all the measurements (MoCA, Montreal Cognitive Assessment), anthropometric and body composition measure, SARC-F (strength, assistance with walking, rising from a chair, climbing stairs, and falls) questionnaire, handgrip strength; and physical functional performance (timed up and go and 6-m walk test). This is a cross sectional study with the sarcopenia diagnostic criteria based on t-score made from younger healthy (reference group). We showed cutoff changed in all measure compared to worldwide parameters, calf circumference should be <32 cm, handgrip strength test <20.7 kgf, appendicular segment muscular mass <5,37 kg/m2, 6-m walking test velocity <1.86 m/s, and timed up and go time >6.65 s. In summary, health professionals and researchers involved with older adult women should consider specific population outcomes application, positive-false diagnostic of sarcopenia could be avoided, and more realistic diagnostic will be reached.